Cooperation of Kazakhstan and Iran in higher education and science - Kussainova A.M., Tyulyubayeva A.U., Turkhanova A.Zh., Ibragimova G.E., (Opción, 2019)
The purpose of the study is to identify the reasons for the low level of interaction between Kazakhstan and Iran. It also develops solutions and identifies prospects for mutual cooperation in this area via comparative qualitative research methods. As a result, the existence of a not sufficiently developed contractual and legal basis was confirmed. In conclusion, until Kazakhstan and Iranian parties sort out priorities in cooperation in the field of science and higher education, do not decide on the need of exchange experience, the state of cooperation in this area will remain at the same level as today.